Interactive android phonic reading for preschool children / Hawa Mohd Ekhsan, Jiwa Noris Hamid and Muhammad Mohd Sobri - Mohd Ekhsan, Hawa; Noris Hamid, Jiwa; Mohd Sobri, Muhammad (UiTM Cawangan Perlis, 2017)
The learning process at preschool level becomes more important in early education for children. Suitable learning tools need to be used by teachers in order to enhance the learning process. Due to that reason, this Android phonic reading application has been developed for preschool children since the technology can attract and engage children's attention. This application is known as 'Kenali ABC' and focuses on the phonic reading approach. This application has been tested using the usability test on the targeted users including preschool children, preschool teachers and Universiti Teknologi Mara (UiTM) lecturers as the experts. The results of the usability test indicate that the application has potential to be used as an alternative method in reading using phonic technique.